Esthétiques sonores et transsensorielles du rapport à la ville dans les parcs et jardins urbains - Jeanne Lafon (Projets de Paysage)
This article takes a look at how parks and gardens with different landscape structures relate to their urban environment acoustically. Although the majority of users seem to appreciate the sound quality of urban parks and gardens and consider them as isolated spaces protected from the city and traffic noise, this is the expression of idealised representations and does not reflect the real situation. In urban areas such spaces are permeable to urban sounds. Instead of considering the acoustic quality of gardens in relation to the city from a binary perspective with, on the one hand, isolated gardens, and on the other, gardens which are acoustically transparent, the article reveals the fact that there are diverse acoustic city-garden interactions, based on the different senses and on symbolic, emotional and functional values pertaining to different landscape structures.